PAM recognition by miniature CRISPR–Cas12f nucleases triggers programmable double-stranded DNA target cleavage - Karvelis, Tautvydas (Nucleic Acids Res, 2020)
In recent years, CRISPR-associated (Cas) nucleases have revolutionized the genome editing field. Being guided by an RNA to cleave double-stranded (ds) DNA targets near a short sequence termed a protospacer adjacent motif (PAM), Cas9 and Cas12 offer unprecedented flexibility, however, more compact versions would simplify delivery and extend application. Here, we present a collection of 10 exceptionally compact (422–603 amino acids) CRISPR–Cas12f nucleases that recognize and cleave dsDNA in a PAM dependent manner. Categorized as class 2 type V-F, they originate from the previously identified Cas14 family and distantly related type V-U3 Cas proteins found in bacteria. Using biochemical methods, we demonstrate that a 5′ T- or C-rich PAM sequence triggers dsDNA target cleavage. Based on this discovery, we evaluated whether they can protect against invading dsDNA in Escherichia coli and find that some but not all can. Altogether, our findings show that miniature Cas12f nucleases can protect against invading dsDNA like much larger class 2 CRISPR effectors and have the potential to be harnessed as programmable nucleases for genome editing.